Inside the black box: the development of proposed rules and the limits of procedural controls - West, William F. (2009)
The need to develop specific proposals as a basis for formal participation ensures the most important policy decisions in rulemaking are often made before notice-and-comment requirements come to bear. Although informal stakeholder participation in the development of proposed rules is common, it tends to be unstructured and idiosyncratic and to lack the assurance of openness that characterize the comment phase of the process. These observations have important implications for our understanding of the effects and the limitations of procedural constraints on bureaucratic policy making. - Reproduced.
Keywords: Public administration